Examining the Determinants of Russian Students’ Intention to Pursue Educational Programs in Malaysia - Elena, Shvets (2013)
One can see that the world has become independent, whereby physical borders have been transformed into transparent nets, allowing and leading to the continuous movement of wealth, information and human talents, and so forth across the Globe. The continuous globalization has brought significant changes to the lives of human beings. One of them is the increasing mobility of students to participate in overseas study. Due to the increasing globalization, the message specifically addressed to students seeking higher education opportunities, is that they must be prepared to face challenges in an extremely competitive global marketplace (Durbin, 2006). In addition, the exposure to and the understanding of different cultures and customs have become important criteria for the potential employment opportunities. The importance of participating in study abroad has been recognized by both undergraduates and post-graduates. But the factors which influence students’ intention to pursue study abroad are debatable. Therefore, the theory of Planned Behavior as a ‘theoretical lens’ is used in this study as it allows the determining of the factors influencing students’ intentions to participate in overseas study. The insufficient available information creates challenges for the marketers to develop the campaigns that can really influence the final decision to pursue study abroad programs. This research examines the determinants of the Russian students’ intention to pursue educational programs in Malaysia. A survey is targeted to 351 undergraduates enrolled into linguistic courses at two universities in Vladivostok, Russia. Various factors have to be considered and analyzed in the planning and developing of meaningful campaigns that will influence Russian students’ intention to pursue their education in Malaysia.